2020
DOI: 10.1155/2020/4121483
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of Shenling Baizhu through PI3K‐Akt‐mTOR Signaling Pathway in a Mouse Model of Bone Metastasis with Small‐Cell Lung Cancer

Abstract: Shenling Baizhu additive powder (SLBZ-AP), a formulation of a variety of natural medicinal plants, has clinical efficacy in treating cancers in previous studies. We explored the effect of SLBZ-AP in bone metastasis of lung cancer (BMLC) mice, and the possible mechanism involved was further investigated in the present study. Mice model of BMLC was made and treated with SLBZ-AP. Pain behavioral tests were performed to explore the effect on BMLC-induced pain in mice. TUNEL staining was used to investigate apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Traditionally, SBP is used to treat inflammation, antioxidants, immunomodulators, and to promote apoptosis ( Tang et al, 2020 ; Wang et al, 2021 ; Pan et al, 2021 ). Inflammatory diseases, endocrine diseases, tumors, and other diseases have been demonstrated to benefit from it ( Tang et al, 2020 ; Feng et al, 2020 ). Specifically, this study investigated the potency of SBP on AHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, SBP is used to treat inflammation, antioxidants, immunomodulators, and to promote apoptosis ( Tang et al, 2020 ; Wang et al, 2021 ; Pan et al, 2021 ). Inflammatory diseases, endocrine diseases, tumors, and other diseases have been demonstrated to benefit from it ( Tang et al, 2020 ; Feng et al, 2020 ). Specifically, this study investigated the potency of SBP on AHR.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional Chinese herbal compound Shenling Baizhu powder (SBP) is used to treat inflammation, antioxidants, immunomodulators, and to promote apoptosis ( Tang et al, 2020 ; Wang et al, 2021 ; Pan et al, 2021 ). It has shown significant value in inflammatory diseases, endocrine diseases, tumors and other diseases ( Tang et al, 2020 ; Feng et al, 2020 ). However, the effect of the SBP compound on PCOS and PMO is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it can activate the PI3K-Akt-mTOR signaling pathway, adjust the microenvironment of the intestinal flora, and improve immunity. [ 15 , 17 , 18 ] Te-Hsin Chao et al found that SLBZS can stimulate the secretion of ghrelin to increase food intake and has potential anti-tumor effects. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] The SLBZS has clinical effects on the treatment of LC, which possible mechanisms of action include activation of PI3K-Akt-mTOR Signaling Pathway and inhibition of tumor growth promoters and antiapoptotic proteins enhances proapoptotic proteins. [ 15 , 16 ] Moreover, SLBZS can adjust the microenvironment of the intestinal flora, improve the body's immunity, and ultimately increase the efficacy of chemotherapy and reduce the side effects. [ 17 , 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al recently published the effect of a Chinese medicinal formula, Baizhu Additive Powder (SLBZ-AP), on the pain control and survival of mice with metastatic lung cancer to the bone. It is postulated that SLBZ-AP partially exerts its effects through the PI3K/AKT/mTOR pathway [ 22 ].…”
Section: Molecular Pathways Involved In Sclc Development and Progrmentioning
confidence: 99%